Psychometric properties and measurement invariance of the Malay version of the YouTube Addiction Scale among university students - Nguyen, Tram Thi Bich; Gan, Wan Ying; Huang, Yu Ting; Tung, Serene En Hui; Poon, Wai Chuen; Siaw, Yan Li; Tham, Weng See; Griffiths, Mark D.; Pakpour, Amir H.; Lin, Chung-Ying; Huang, Po Ching (SAGE Publications, 2026)
The primary objectives of the present cross-sectional study were to translate and culturally adapt the YouTube Addiction Scale (YAS) into Malay and to evaluate its reliability, factorial validity, concurrent validity, and measurement invariance across gender and ethnicity among Malaysian university students. A total of 690 students participated (mean age = 21.29 years [SD ± 2.42]; 74% female). Confirmatory factor analysis supported a unidimensional YAS structure with good fit (CFI = 0.98, TLI = 0.97, SRMR = 0.06, RMSEA = 0.07). The scale exhibited strong reliability (α = 0.83, ω = 0.84) and measurement invariance across gender and ethnicity. YAS scores showed correlation with Smartphone Application-Based Addiction Scale score (r = 0.17, p < 0.001) and Bergen Social Media Addiction Scale score (r = 0.23, p < 0.001), a weak correlation with time spent on social media (r = 0.09, p = 0.02), and no significant relationship with time spent on online gaming (r = 0.03, p = 0.47). The Malay YAS is a reliable and valid instrument for assessing YouTube addiction among Malaysian university students. Its unidimensional structure, strong reliability, robust measurement invariance across gender and ethnicity, and satisfactory concurrent validity support its application in research, screening, and intervention programs.